MEDIA FRAMES AND NARRATIVES ABOUT DRUGS AND ALCOHOL: HOW MEDIA SHAPES PUBLIC PERCEPTION - Valentina MARINESCU; Anda Anca RODIDEAL; Cornelia RADA; Alexandra Elena NEAGU; Mihaela LUNGU (Anthropological Researches and Studies)
Objectives. The objectives of this research paper are to identify the frames used by online journalists in covering the acts of violence done by teenagers involving alcohol and/or drug consumption, study realised during the two publicized events with the aim to analyze the similarities and the differences during the media coverage of these incidents across in both cases. Material and methods. The research used the narrative analysis in order to examine how online media presented violent acts by teenagers under the influence of drugs or alcohol. The analysis focused on identifying key narrative structures, such as characters, conflicts, and themes, in 60 online news articles. The sample included the coverage of two widely publicized events in Romania: the “Medusa operation” (20 articles) and the 2 Mai commune accident (40 articles), published between January 2023 and September 2024. The selection was based on media attention and relevance to drug or alcohol consumption. Results. The analysis partially confirmed the first hypothesis, with episodic frames prevailing only in the 2 Mai commune accident, while the “Medusa Operation” was framed thematically, focusing on institutional actions. The second hypothesis was not confirmed, as both cases shared common themes around the criminalization of drug use without case-specific narratives. Conclusion. The media’s tendency to oversimplify narratives by focusing on general themes and stereotypical portrayals limits public understanding of the complexities of drug use among adolescents, missing opportunities to discuss prevention and rehabilitation.